Detection for physical-layer network coding in two-way relay channels - Wei YAN; Yue-ming CAI; Cheng-kang PAN (Tongxin xuebao)
The detection for physical-layer network coding (PNC) in two-way relay channels was investigated.Maximum-likelihood (ML) detection not only had great performance but also had high computational complexity.Therefore,without channel state information (CSI) at source nodes,two detection schemes were proposed.The first scheme was likelihood ratio(LR)detection based on LR function,and the other was maximum a posteriori probability (MAP) detection based on MAP rule.Meanwhile,It carried out similar analysis if CSI was available at source nodes.Compared to ML detection which separately detects two source messages,numerical and simulation results show that LR detection outperforms it in terms of BER metric with the requirement for additional noise variance information.And MAP detection is equivalent to ML detection,and it has lower computational complexity.